InCVAX – A novel strategy for treatment of late-stage, metastatic cancers through photoimmunotherapy induced tumor-specific immunity. Issue 2 (10th April 2015) - Zhou, Feifan; Li, Xiaosong; Naylor, Mark F.; Hode, Tomas; Nordquist, Robert E.; Alleruzzo, Luciano; Raker, Joseph; Lam, Samuel S.K.; Du, Nan; Shi, Lei; Wang, Xiuli; Chen, Wei R.
Highlights Laser immunotherapy (LIT) is a novel cancer treatment strategy that uses local photothermal irradiation and a local immunological stimulation. A novel immunoadjuvant, glycated chitosan (GC), was developed to work with laser interaction to creates an in situ autologous cancer vaccine (inCVAX). Furthermore, inCVAX has been administered in initial clinical trials for the treatment of patients with metastatic breast cancer with promising outcomes.